2018
DOI: 10.1103/physrevlett.121.030606
|View full text |Cite
|
Sign up to set email alerts
|

Integrable Trotterization: Local Conservation Laws and Boundary Driving

Abstract: We discuss a general procedure to construct an integrable real-time Trotterization of interacting lattice models. As an illustrative example, we consider a spin-1/2 chain, with continuous time dynamics described by the isotropic (XXX) Heisenberg Hamiltonian. For periodic boundary conditions, local conservation laws are derived from an inhomogeneous transfer matrix, and a boost operator is constructed. In the continuous time limit, these local charges reduce to the known integrals of motion of the Heisenberg ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
126
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 85 publications
(139 citation statements)
references
References 34 publications
(37 reference statements)
9
126
0
Order By: Relevance
“…Furthermore, it was shown that this family includes both integrable [60][61][62] and non-integrable cases. In particular, it contains a full parameter line of the integrable trotterized XXZ chain 61,62…”
Section: The Dual-unitary Dynamicsmentioning
confidence: 99%
“…Furthermore, it was shown that this family includes both integrable [60][61][62] and non-integrable cases. In particular, it contains a full parameter line of the integrable trotterized XXZ chain 61,62…”
Section: The Dual-unitary Dynamicsmentioning
confidence: 99%
“…Since a direct computation of higher conserved charges is tedious, it would be of interest if the conserved charges of the model could be equipped with a boost 10Žiga Krajnik, Tomaž Prosen operation that would facilitate their automated computation, similarly as in the quantum case [21].…”
Section: Integrability Of the Modelmentioning
confidence: 99%
“…Although MBL can protect [40][41][42] Floquet topological phases [20,[43][44][45][46][47][48][49][50][51][52], these phases are localized and do not host chiral modes. However, in addition to MBL systems, interacting integrable systems are another broad class of systems-including the canonical Hubbard, Heisenberg, and Lieb-Liniger models-that do not heat up to infinite temperature [53][54][55]; whether distinctively Floquet versions of these models exist has been less discussed [56][57][58][59].…”
mentioning
confidence: 99%